Antibodies to chicken anaemia virus (CAV) in poultry reared in our country - GEORGOPOULOU (Ι. ΓΕΩΡΓΟΠΟΥΛΟΥ) J.; IORDANIDIS (Π. ΙΟΡΔΑΝΙΔΗΣ) P. (Journal of the Hellenic Veterinary Medical Society, 2018)
Two handred fifty eight serum samples collected from 39 poultry flocks were tested for detecting antibodies to chicken anaemia virus (CAV) by ELISA method. One handred four blood serums were collected from 11 broiler breeder flocks aged 1 day to 9,5 months, 147 from 26 broiler breeder flocks aged 1 to 45 days and 7 from 2 commercial layer flocks aged 4 in 15 days. Antibody to CAV were detected in five broiler breeder flocks aged 70 days, 2,5, 5,5, 6 and 9,5 months respectively and in 15 broiler flocks from which 2 of them aged 1 day and the other 13 flocks aged 8, 15,16, 28, 38, 42, 43 and 45 days respectively. The detection of positive serums supports our clinical observations about the presence of chicken aneamia infection principally in broiler flocks in our country.